Is Muscular Fitness Associated with Future Health Benefits in Children and Adolescents? a Systematic Review and Meta-Analysis of Longitudinal Studies - Garcia-Hermoso, A (Springer International Publishing, 2019)
Background: No previous systematic review has quantitatively examined the association between muscular fitness during childhood and adolescence and health parameters later in life. Objective: The aim was to systematically review and meta-analyze the current evidence for a prospective association between muscular fitness in childhood and adolescence and future health status. Methods: Two authors systematically searched MEDLINE, EMBASE and SPORTDiscus electronic databases and conducted manual searching of reference lists of selected articles. Relevant articles were identified by the following criteria: apparently healthy children and adolescents aged 3–18 years with muscular fitness assessed at baseline (e.g., handgrip, standing long jump, sit-ups, among others), and a follow-up period of ≥ 1 year. The outcome measures were anthropometric and adiposity measurements and cardiometabolic, bone and musculoskeletal health parameters. Two authors independently extracted data. Results: Thirty studies were included in the meta-analysis, yielding a total of 21,686 participants. The meta-analysis found a significant, moderate-large (p < 0.05) effect size between muscular fitness at baseline and body mass index (r = − 0.14; 95% confidence interval (CI) − 0.21 to − 0.07), skinfold thickness (r = − 0.32; 95% CI − 0.40 to − 0.23), homeostasis model assessment estimated insulin resistance (r = − 0.10; 95% CI − 0.16 to − 0.05), triglycerides (r = − 0.22; 95% CI − 0.30 to − 0.13), cardiovascular disease risk score (r = − 0.29; 95% CI − 0.39 to − 0.18), and bone mineral density (r = 0.166; 95% CI 0.086 to 0.243) at follow-up. Conclusion: A prospective negative association was observed between muscular fitness in childhood/adolescence and adiposity and cardiometabolic parameters in later life, together with a positive association for bone health. There is inconclusive evidence for low back pain benefits. © 2019, Springer Nature Switzerland AG.